ROMBONGAN PERKEBUNAN PARAKAN SALAK SUKABUMI DI AMSTERDAM TAHUN 1883: GAMELAN PARAKAN SALAK - Nugraha, Asep (Paraguna, 2018)
In   1883  the  tea _plantation  in  the  Parakan  Salak  Sukabumi  region brought workers from  the  local  plantation  community to  Amsterdam,  to  participated in De Internationale Koloniale en  Uitvoerhandel Tentoonstelling. Planter, Mr.  Holle, promoted the  commodity of tea by including the original culture of the  land of the colony,  precisely the  Sundanese  ethnicity.   Sundanese  cultural  presentations include  gamelan  and   dance  performances  and    cultural  tours  of  Sundanese villages.  The moment was the first time  Europeans  directly witnessed people from the  colonies played  music  and   danced  and   carried  out  activities  of daily   life through village activities.  This  paper describes the  existence of the  Parakan Salak plantation group in Amsterdam in  1883.